The intermingled meanings of PhoneMe: Exploring transmodal, place‐based poetry in an online social network. Issue 4 (5th December 2022) - Horst, Rachel; James, Kedrick; Morales, Esteban; Takeda, Yuya
Abstract: This research paper explores how preservice teachers engaged with the transmodal place‐based poetry on PhoneMe, an educational social media platform for sharing poetry and vocal performances about place. This work is situated in literature on digital place‐based education and theoretical scholarship exploring transmodality and the shifting entanglement of meanings and modes. In this paper, we share findings from a research survey conducted with teacher candidates in a core teacher education literacy course that had transitioned online due to the COVID‐19 pandemic. We discuss how participants engaged with the transmodal poetry in the survey and how their perceived poetic meaning and poetic connections changed with each additional modality. We share the pedagogical implications of our findings as well as ideas gleaned from the data for integrating the PhoneMe platform and pedagogy in secondary school classrooms. In the discussion, we explore how engagement with transmodal place‐based digital poetry can be a unique way to draw together place‐based education, digital literacies, social media literacies, and poetry pedagogy in a way that is visceral, relational, and highly relevant to contemporary lives and classrooms both on and offline.